Modalité, dialogisme et stratégies discursives - Marion Bendinelli (Anglophonia)
This article studies the dialogic effects of the various uses of the modal auxiliary MAY within American presidential debates. Firstly, we adopt the analytic framework of Antoine Culioli (1990) called Théorie des Opérations Énonciatives and show that these dialogic effects are generated by some fundamental metalinguistic operations among which the construction of notional alterity. As a consequence, it seems possible to define MAY as a dialogic marker (Bres et Mellet 2009) since it is its intrinsic properties (and not the context) that cause dialogic effects. Secondly, we suggest that the framework developed here sheds new light on some of the discursive strategies employed by the candidates; in particular, it helps provide a linguistic account of manipulative discourse. Finally, the study considers the relations between the notions of alterity and dialogism.